Audits by Comptroller and Auditor General of India and Their Contribution to Accountability in Development Cooperation Projects - Chatterjee, Shourjo; Verma, Rajit (Indian Journal of Finance, 2022)
Audit of development cooperation projects by the Comptroller and Auditor General of India (CAG) contributes to ensuring accountability in using development cooperation funds. The present study examined such contribution to five different types of accountability: financial accountability, compliance accountability, performance accountability, accountability to stakeholders, and constitutional accountability based on the analysis of findings presented in the CAG’s audit reports. The study examined the audit reports for six states of India â€“ Andhra Pradesh, Assam, Gujarat, Madhya Pradesh, Uttarakhand, and West Bengal for six years with findings on World Bank and Asian Development Bank projects. The sample states were selected based on stratified random sampling, with one state each drawn from each of the six geographical regions of India. Further, the study analyzed three essential aspects of management of development cooperation projects such as project planning, project implementation & monitoring, and financial management, along with their relevant sub-categories like the number of findings; money value as a measure of the materiality of the findings; and the yearly consistency. The study’s conclusions based on the different findings presented in audit reports revealed that CAG’s audit reports contributed substantially to the respective types of accountability.